The Effect of ESG, Operational Capacity, Claim Ratio, and Liquidity on Financial Distress of Insurance Companies Moderated by Risk-Based Capital - Mahendra, Bhima; Siswanti, Indra (IJOSMAS, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG), operational capacity, claim ratio, and liquidity on financial distress in Indonesian insurance companies, with Risk-Based Capital (RBC) as a moderating variable. Using a quantitative approach with saturated sampling, the study analyzed 18 insurance companies listed on the Indonesia Stock Exchange. Panel regression with EViews 12 was applied to test the hypotheses. The results show that ESG and liquidity do not significantly affect financial distress, while operational capacity has a positive effect and claim ratio has a negative effect. Moreover, RBC does not moderate the relationship between ESG or liquidity and financial distress but significantly strengthens the effects of operational capacity and claim ratio. These findings highlight the importance of operational efficiency and claim management in reducing financial distress, while emphasizing the role of RBC as a financial safeguard in the insurance industry.